Policing and Carcerality in Public Libraries - Gleason, Sean; Ridsdale, Ash; Maddaford, Monica; De'Ath, Alyssa (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2025)
Policing in libraries poses a significant barrier to access for many potential patrons—and yet, much of the literature on library security advocates for strong security measures without regard for the safety and wellbeing of patrons and staff who are BIPOC, LGBTQ2SIA+, disabled, and unhoused. Considerable lived experience and research shows that police disproportionately target those whose identities deviate from the norm, but in a society with so many diverse experiences, identities, and relationships to power and authority, we are obligated as socially conscious library workers to consider how our relationships to policing and security in the library affect all peoples. To do so, we draw on an intersectional abolitionist praxis that seeks to deconstruct the carceral and penal systems omnipresent in our society. After exploring some of the security measures taken by public libraries that enable the carceral state, we propose alternative measures that can be taken through the acronym-based catchphrase to encourage library workers of all types to give greater consideration to the ramifications of involving police in difficult patron interactions.